Chronic critical illness after hypothermia in trauma patients. Issue 1 (29th July 2021) - Miranda, David; Maine, Rebecca; Cook, Mackenzie; Brakenridge, Scott; Moldawer, Lyle; Arbabi, Saman; O'Keefe, Grant; Robinson, Bryce; Bulger, Eileen M; Maier, Ronald; Cuschieri, Joseph
Abstract : Objectives: Chronic critical illness (CCI) is a phenotype that occurs frequently in patients with severe injury. Previous work has suggested that inflammatory changes leading to CCI occur early following injury. However, the modifiable factors associated with CCI are unknown. We hypothesized that hypothermia, an early modifiable factor, is associated with CCI. Methods: To determine the association of hypothermia and CCI, a secondary analysis of the Inflammation and Host Response to Injury database was performed, and subsequently validated on a similar cohort of patients from a single level 1 trauma center from January 2015 to December 2019. Hypothermia was defined as initial body temperature ≤34.5°C. CCI was defined as death or sustained multiorgan failure ≥14 days after injury. Data were analyzed using univariable analyses with Student's t-test and Pearson's χ 2 test, and logistic regression. An arrayed genomic analysis of the transcriptome of circulating immune cells was performed in these patients. Results: Of the initial 1675 patients, 254 had hypothermia and 1421 did not. On univariable analysis, 120/254 (47.2%) of patients with hypothermia had CCI, compared with 520/1421 (36.6%) without hypothermia who had CCI, p<0.001. On multivariable logistic regression, hypothermia was independently associated with CCI, OR 1.61 (95% CI 1.17 to 2.21) but not mortality. Subsequent validation in 1264 patients of which 172 (13.6%) were hypothermic, verified that hypothermia was independently associated with CCI on multivariable logistic regression, OR 1.84 (95% CI 1.21 to 2.41). Transcriptomic analysis in hypothermic and non-hypothermic patients revealed unique cellular-specific genomic changes to only circulating monocytes, without any distinct effect on neutrophils or lymphocytes. Conclusions: Hypothermia is associated with the development of CCI in severely injured patients. There are transcriptomic changes which indicate that the changes induced by hypothermia may be associated with persistent CCI. Thus, early reversal of hypothermia following injury may prevent the CCI. Level of evidence: III.